Cultivation parameters and the white spot disease in shrimp farms in Santa Catarina, Brazil - Costa, Sérgio Winckler da; Vicente, Luiz Rodrigo Mota; Souza, Talita Medeiros de; Andreatta, Edemar Roberto; Marques, Maria Risoleta Freire (Pesquisa Agropecuaria Brasileira, 2011)
<!–[if gte mso 9]> Normal 0 <![endif]–> The objective of this work was to evaluate the relationship among physicochemical and biological parameters in shrimp cultivation with the disease caused by the white spot syndrome virus (WSSV). The occurrence of mortality, physical and chemical characteristics of water and soil were evaluated, and clinical and microscopic analyses and the presence of vibrio in hemolymph, were performed as well as the histopathological and molecular diagnosis (PCR) of the WSSV in ponds of eight farms in Santa Catarina, Brazil, between 2008 and 2009. The virus was detected in five farms, which had displayed the disease in previous cycles. The temperature of the water was similar among farms independently of the presence of the virus, and mortality occurred at ascendant temperature intervals, between 24.6 and 29.3ºC. No significant differences were found for the parameters of microscopic analyses among ponds either with or without the virus. Nitrite, silica, phenol and water-alkalinity concentrations, as well as soil pH values, showed significant differences among the ponds affected or not by the WSSV. Nitrite, silica and pH values were within the recommended limits for shrimp cultivation, however this did not occur for the alkalinity and phenol concentrations, wich suggests a relationship of the latter parameters with manifestation of the white spot disease.